Pengaruh Kecepatan Kendaraan Terhadap Keselamatan Pengguna Kendaraan Bermotor Pada Simpang Tak Bersinyal - Prima Juanita Romadhona; Sholihin Ramdhani (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Unsignalized intersection at Jl. Kaliurang Km 13 -Jl.Besi Jongkang, Yogyakarta has traffic flow increased. Vehicles meet from various directions in the intersection and not equipped with traffic control resulting potential traffic conflicts that can eventually lead to an accident. A factor most causing the accident is speed. The purpose of this study was to find out the effect of the speed towards the motorized safety at unsignalized intersection. Traffic Conflict Technique (TCT) is a method of predicting an accident by the conflict in intersection or road. This method requires some data such as vehicle speed (km/h) and a range of conflict (m) that can be obtained the time to accidents (S) which the conflict can be known to serious or non serious conflict. If a conflict included into the category of serious conflict, the conflict has a potential to cause an accident. Finally, TCT method results show that the unsignalized intersection at Jl. Kaliurang Km 13 -Jl. Besi Jongkang have 76.9% potencial of accidents with an average speed of serious conflict is 26.24 km/h. However, the range distance for conflict only 2.0-3.5 m so the potential of accident increased.